(untitled) (Bangladesh Journal of Nuclear Agriculture, 2025)
An experiment was conducted to study the morpho-physiological parameters and yield indices at three locations (HQs, Rangpur and Magura substations) of Bangladesh Institute of Nuclear Agriculture (BINA) with four varieties during Aman season (July-December). The aim of this study was to evaluate the performance based on morpho-physiological characteristics and yield attributes of some BINA released modern Aman rice varieties. The rice varieties were viz., Binasail, Binadhan-7, Binadhan-11 and Binadhan-12. The experiments were set following RCBD design with three replications. The physiological parameters like chlorophyll content, photosynthesis rate and nitrate reductase activity showed initially higher values and decreased gradually with age. The yield-contributing characters were the highest in Binadhan-7, thereby grain yield, followed by Binadhan-11. The lowest grain yield was recorded in Binasail for its lower yield attributing traits. Although location did not effect on yield but in terms of interaction with location Binadha-7 performed better in Mymensingh followed by Rangpur and Magura. Bangladesh J. Nuclear Agric, 39(2): 77-86, 2025